PROGRAM KECAKAPAN WIRAUSAHA SEBAGAI ALTERNATIF PENDIDIKAN KETERAMPILAN DALAM MENJAGA KESTABILAN PANGAN KELUARGA - Adang Danial; Wiwin Herwina; Mumu Mumu; Nastiti Novitasari (IKIP SILIWANGI, 2021)
The general purpose of this community service is to facilitate the community in obtaining new livelihoods during the COVID-19 period. To be able to adapt to new livelihoods, people must be equipped with skills that suit the needs of the business world, one of the alternatives is through an entrepreneurial training program (PWK). The external type of community service activities is expected to improve people's skills to work and entrepreneurship to support family income that leads to family food security. Based on the findings in the field obtained information that the program participants feel that the PWK program is considered suitable for the community amid the limitations of the community in recognizing the potential, so that most program participants expect this activity to be carried out continuously in order to improve the skills of program participants. Furthermore, the participants of this program hope that this program can be equipped with assistance in pioneering efforts. The target set in the community service food security scheme (Pbm-KP) is to provide training to the community in District Cibeureum through the PWK program so that the community acquires knowledge and skills to increase family income so that it is ultimately able to maintain the stability of family food security. The implementation team in this service as many as three people who are lecturers majoring in public education FKIP UNSIL.